How Banyumas people 'describe' G30S/PKI in the novel Ronggeng Dhukuh Paruk - Khristianto Khristianto; Widya Nirmawalati (English, 2018)
The novel Ronggeng Dukuh Paruk (RDP) came out in 1982, when the new order regime was still firmly established. One of the important criticisms in the work was the 'incorrect' handling of communism by the government at that time following the eruption of the G30S/PKI history. The author of the novel tries to bring a different view of the issue. This paper tries to present how the original Banyumas personified the political turmoil-how the laypeople interpreted the events that had consumed them as victims, or the sacrificed. Based on the recurrent reading of the Indonesian-language RDP novel and Javanese language Banyumasan, the authors firmly state that the people of Dukuh Paruk are merely victims of the outside world. People of Dukuh Paruk have no idea what they have to do, other than that they want to perpetuate the tradition they are proud of i.e. Ronggeng. Nor do they blame or think that they are people outside of those who have committed crimes against them. The disaster that befall them is none other due to their mistakes that they do not run the rituals that must be done before performances of ronggeng. The old people of Dukuh Paruk also realized that the disaster called pageblug had been signaled by the appearance of the latitude of the cubes (comets), and they had ignored the cue. Thus, pageblug should be accepted. Against the innocence of clean thought, the author asserts that something is wrong with them, systematically practiced by the regime at that time. He agreed that the coup was false; but the way in which the state deals with such problems is also unjustifiable. The state has clearly punished many Indonesians without trial, and killed thousands of innocent people.